Target-specific expression of pre- and postsynaptic mechanisms - Tóth, Katalin (Blackwell Science Inc, 2000)
Target-specific expression of pre- and postsynaptic mechanisms of synaptic transmission has been shown in a variety of central neurons by a number of laboratories. These data have demonstrated that synaptic transmission between single axons diverging onto distinct target neurons can behave independently, differentially influencing activity in the target neuron. Similarly, single neurons are capable of manufacturing molecularly distinct ligand-gated receptors and targeting them to synapses innervated by distinct converging afferent projections. A picture is emerging consistent with a role for both pre- and postsynaptic mechanisms in influencing the target-specific nature of transmission at numerous diverse synapses throughout the mammalian CNS. This target specificity adds another level of complexity in unravelling the roles played by individual neurons within a computational network. To begin to understand the coordinated activity of large ensembles of neurons it is becoming clear that the nature of transmission between individual pre- and postsynaptic elements within a circuit must first be understood for each and every neural element involved.